THE EFFORTS TO IMPROVE UNDERSTANDING OF MENTAL HEALTH THROUGH EARLY DETECTION OF MENTAL DISORDERS EDUCATION - isti antari; Agus Widyawati; Mi'rojul Husna (LPPM STIKES Madani, 2022)
The prevalence of mental emotional disorders such as depression and anxiety in people aged > 15 years in Indonesia has increased from 6.0 to 9.8 per 1000 population. DIY is one level higher than the national figure, which is in the range of 10 per 1000 population. The Ministry of Health has launched the handling of mental health problems based on a healthy paradigm where prevention and promotive efforts are more emphasized than treatment efforts. Education received by the community so far is still in the form of knowledge about physical illness. The implementation of this community service activity aims to provide knowledge about early detection of mental disorders. The participants of this activity were PKK and Posyandu cadres. From this activity, the average pre-test score was 34% and the post-test average after the activity was 83%. Health education can be used to increase knowledge about early detection of mental disorders in the community